Lipoprotein(a) and cardiovascular outcomes in patients with coronary artery disease and impaired glucose metabolism. (3rd October 2022) - Sa, D; Palma Dos Reis, R; Santos, M; Temtem, M; Sousa, A C; Henriques, E; Rodrigues, M; Freitas, S; Borges, S; Ornelas, I; Drumond, A; Mendonca, M I
Abstract: Introduction: Lipoprotein(a) [Lp(a)] is an LDL-like molecule composed of a part of apolipoprotein(a) bounding covalently to apolipoprotein B-100. High plasma Lp(a) levels were associated with MACE in stable CAD patients. Recent research shows contradictory results in stable CAD patients with high Lp(a) plasmatic levels and impaired glucose metabolism in MACE occurrence. Purpose: Investigate whether high Lp(a) levels were associated with MACE in CAD patients with impaired glucose metabolism, at an extended follow-up. Methods: A prospective cohort of 1, 127 CAD patients with impaired glucose metabolism (pre-diabetes and diabetes) was observed during 4.9±3.4 years. Pre-diabetes was considered when fasting plasma glucose ranged from 5.6 to 6.9 mmol/L, or hemoglobin A1c levels ranging from 5.7 to 6.4%. Lp(a) levels ≥30 mg/dL were considered high. Bivariate and multivariate Cox regression analysis evaluated the risk of Lp(a) ≥30 mg/dL for MACE occurrence. Kaplan-Meier curves estimated the survival probability for high and low Lp(a) levels. Results: Of the patients with Lp(a) levels ≥30, 44.4% presented MACE and 32.0% had no MACE (p<0.0001). Cox regression analysis with smoking, hypertension, dyslipidemia, physical inactivity and kidney failure (creatinine clearance <60 mL/min) showed that high Lp(a) remained in the equation as an independent risk factor for MACE (HR=1.24; p=0.031). The Kaplan-Meier showed, at 10-year' follow-up, a better survival in the group with lower Lp(a) levels (p=0.023). Conclusion: Our study demonstrated that high Lp(a) levels were an independent predictor of MACE and cardiovascular mortality in a CAD population with impaired glucose metabolism. Lp(a) measurement may help further risk stratification for diabetes and pre-diabetes patients suffering CAD. With the recent development of drugs that selectively lower Lp(a) levels, this marker can become a clinical target for reducing CVD risk. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): SESARAM EPERAM